Construction of characterization parameters of algal photosynthetic inhibition method for detection of comprehensive toxicity in water. (March 2022) - Gu, Mengyuan; Yin, Gaofang; Gan, Tingting; Zhao, Nanjing; Qi, Peilong; Chen, Min; Ding, Zhichao; Jia, Renqing; Liu, Jinjing; Ma, Mingjun; Yang, Ruifang; Fang, Li; et al.
Highlights: Provides a more stable and efficient photosynthetic fluorescence parameter to detect comprehensive toxicity in water. The point J and point I in the OJIP curve have different response to toxic substances. The surrounding area under the OJIP curve will vary with the different degrees of electron blocking. Using the maximum and minimum normalization method to eliminate the influence of the absolute intensity of the fluorescence. Assign weights to different data items to improve detection sensitivity. Abstract: Pollutants in water seriously threaten the health of human beings and will lead to potential ecological risks to the aquatic environment. Researchers use many chemical, physiological and morphological methods to detect the comprehensive toxicity in water. Among them, the photosynthetic inhibition method is considered a powerful method to detect the comprehensive toxicity in water, takes the chlorophyll fluorescence in the body as a natural probe, and determines the toxicity effect of pollutants by measuring the variation of photosynthetic fluorescence parameters. It has the advantages of fast and convenient measurement and real-time online detection. The widely used photosynthetic fluorescence parameters are the maximal quantum yield of photosystem II (Fv/Fm) and performance index PIABS . There are the problems that the sensitivity is not high enough, and the substances that can be detected are limited when researchers use Fv/Fm and PIABS as indicators to detect the comprehensive toxicity in water. So, in this paper, we proposed a construction method of Performance Index of Comprehensive Toxicity Effect (PICTE ) using multi-parameter fusion based on the chlorophyll a fluorescence rise kinetics curve (OJIP) of algae. The fluorescence information of point J and point I in the curve was integrated. The area surrounded by the curve and the time corresponding to point J and point I were weighted for data items to construct PICTE . On this basis, Chlorella vulgaris was used as the tested algae species to compare the performance differences of Fv/Fm, PICTE, PIABS in the detection of toxic substances under the stress of five common water pollutants: Diuron (DCMU, 3-(3, 4-dichlorophenol)-1, 1-dimethylurea), Dibromothymoquinone (DBMIB, 2, 5-dibromo-3-methyl-6-isopropyl-benzoquinone), Methyl viologen (MV, 1, 1ꞌ-dimethyl-4, 4ꞌ-bipyridinium-dichloride), Malathion, Carbofuran. The performance differences of Fv/Fm, PICTE, PIABS in detecting toxic substances, including lowest detection limit, highest response concentration, stability, and reproducibility, were studied. The results show that: in terms of toxicity detection, the constructed PICTE was sensitive to all five toxic substances and could detect more kinds of pollutants than Fv/Fm. The lowest detection limit of PICTE for five toxic substances compared with PIABS was reduced by 74.43%, 77.01%, 67.30%, 60.69%, and 50.81%, respectively. At the same time, it has a stronger ability to detect toxic substances with high concentration. The stability and reproducibility of PICTE for detecting the toxicity of DCMU, DBMIB, Malathion, and Carbofuran were all excellent, and all of the relative standard deviation (RSD) was < 5%. This research provides an important basis for constructing a highly sensitive and high-precision detection method for comprehensive toxicity in water.